Effects of a traditionally prepared Glycyrrhiza glabra root-based beverage on female reproductive function in rats - Kocaoğlu, Merve; Büyüknacar, Hacer Sinem; Cevher, Aslı; Dağlıoğlu, Gülçin; Kılıç Bağır, Emine; Ertuğ, Fatma Peyman; Kıroğlu, Olcay; Göçmen, Cemil (Frontiers in Nutrition, 2025)
Glycyrrhiza glabra (licorice) is widely known for its traditional medicinal uses, including in the form of root-based beverages prepared and consumed in various regions. In Eastern and Southeastern Anatolia, such beverages are commonly consumed as part of daily dietary practices. Despite the widespread use of licorice root, data on the physiological effects of traditionally prepared licorice beverages on the female reproductive system are limited. This study aimed to evaluate the effects of substituting drinking water with a traditionally prepared G. glabra root-based beverage (30 mg/mL/day) for 7 days on female reproductive function in rats. Thirty-two adult female Wistar rats were divided into two main groups: Control and G. glabra; (licorice). Each group was further subdivided based on the estrous cycle into Proestrus/Estrus (P/E) and Diestrus/Metestrus (D/M) phases. Animals were housed in metabolic cages, and the experimental group received freshly prepared root-based licorice beverage instead of drinking water for 7 days. Vaginal smears were used to determine cycle phases. Serum levels of LH, FSH, and estrogen were measured using ELISA. Isolated uterus experiments were conducted to assess spontaneous and oxytocin-induced contractility (1000 mU/mL). Histopathological evaluations were performed on ovarian, liver, and kidney tissues. Compared to controls, the G. glabra group showed a significant increase (p < 0.05) in LH and FSH levels, while estrogen levels remained unchanged. Both spontaneous and oxytocin-induced uterine contractions exhibited significantly reduced amplitude and area under the curve (AUC) in the licorice group. Histological analysis revealed a decrease in the number of corpus luteum during the P/E phase, and an increase in primary and antral follicles during the D/M phase. No significant histopathological alterations were observed in the liver or kidney tissues. These findings suggest that traditional Glycyrrhiza glabra root-based beverages may influence female reproductive function in an estrous cycle-dependent manner, potentially affecting both hormonal regulation and uterine contractility.